IMPLEMENTASI MEDIA PAPAN PINTAR UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG PADA MATERI PENJUMLAHAN DI SANGGAR BIMBINGAN ‘AISYIYAH PANDAN MALAYSIA - Subhi, Harisya; Syamsuyurnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics in Elementary School is often considered as one of the most avoided subjects by students. it causes students to have low learning outcomes. Mathematics learning is not just conveying the knowledge that teachers have to their students, it is a stage to solve more complex problems. The method in this study is PTK. This study aims to determine how the use of smart board media to improve the numeracy skills of class II students on the addition material at the Guidance 'Aisyiyah Pandan Malaysia studio using learning media in the form of Smart Boards. The results show that the average value of Mathematics learning outcomes for students' Addition material in the pre-cycle was 43.33% with classical completeness of 33.3% in the less category. While cycle I shows that the average value of student test results is 64.16% with classical completeness of 58.33% which is in the sufficient category and cycle II the average value of student test results is 82.5 with classical completeness of 83.33% which is in the good category. Thus it can be concluded that the use of smart board learning media can improve students' arithmetic skills in learning Mathematics on Addition material at the 'Aisyiyah Pandan Malaysia guidance studio. By implementing the use of smart board learning media at the Guidance Studio, it is expected that the quality of learning will be improved and students can better understand learning, especially addition material.